Aortic Distensibility Can Predict Events in Patients With Premature Coronary Artery Disease: A Cardiac Magnetic Resonance Study. (April 2021) - Razik, Nady A.; Kishk, Y. T.; Essa, Mohammed; Ghany, Mohamed Abdel
Noninvasive assessment of aortic distensibility (AD) is feasible with cardiac magnetic resonance (CMR). We investigated the relationship between AD (assessed by CMR) and coronary artery disease (CAD) severity (assessed by the SYNTAX score) in patients with premature CAD. We recruited 125 patients with CAD confirmed by coronary angiography (males were <55 years old and females <65 years old). We excluded patients with significant aortic disease or contraindications to CMR. We also recruited 25 age- and sex-matched healthy patients as controls. One-year follow-up was also carried out. Aortic distensibility at the aortic root (AR) and descending aorta (DA) was significantly ( P < .001 for both) lower in the patient group. There was a significant negative correlation between SYNTAX score and AD at the AR (r = −0.56; P < .001) and DA (r = −0.34; P < .001), but insignificant correlation with distensibility at the ascending aorta (AA; r = −0.03; P = .81). AR, AA, and DA distensibility, as well as left ventricular ejection fraction were predictors of adverse events. The severity of CAD in young patients is associated with decreased AD, especially at the level of the AR. Aortic distensibility can predict adverse events in these patients.